2010
DOI: 10.1371/journal.pone.0009212
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CCR5 Expression in Human Placenta: Insights from a Study of Mother-to-Child Transmission of HIV in Malawi

Abstract: BackgroundHuman promoter polymorphisms in the chemokine co-receptor 5 gene (CCR5) have been noted for association with mother-to-child transmission of HIV (HIV MTCT) as well as reduced receptor expression in vitro, but have not been clearly associated with CCR5 expression in vivo. Placental expression of CCR5 may be influenced by such polymorphisms as well as other in vivo regulatory factors.Methodology/Principal FindingsWe evaluated the associations between infant CCR5 polymorphisms, measures of maternal infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This observation raises the possibility that additional amniotic and/or placental factors quell fetal inflammatory intestinal responses in utero. Innate and adaptive placental cellular responses with immunomodulatory and/or antiviral properties have been described (20)(21)(22)(23)(24), and whether these or other factors play a role is uncertain.…”
Section: In Utero Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation raises the possibility that additional amniotic and/or placental factors quell fetal inflammatory intestinal responses in utero. Innate and adaptive placental cellular responses with immunomodulatory and/or antiviral properties have been described (20)(21)(22)(23)(24), and whether these or other factors play a role is uncertain.…”
Section: In Utero Transmissionmentioning
confidence: 99%
“…Intra-epithelial Lymphocytes 20 Gestational age (weeks) 30 40 10 The role of breastfeeding in shaping the composition of infant stool has been appreciated since the early 20th century and today is being refined with culture-independent techniques. Not only does the stool bacterial composition differ between breast-fed and formula-fed infants, the expression of immunity-related genes in intestinal epithelial cells also differs (167).…”
Section: Lamina Propriamentioning
confidence: 99%
“…The mechanism for this association may be related to components of HS proteoglycans, consisting of a core protein bound to HS, involved in HIV MTCT and the fact that the HIV-1 virus and the chemokine RANTES bind to syndecans, core transmembrane proteins which carry HS [72]. An increase in HS3ST3A1 is associated with an increase in the placental chemokine co-receptor 5 gene (CCR5) which is observed with an increase in maternal HIV viral load [73]. As previously noted, temporal lobe epilepsy apoptotic markers, caspase-3, −8, −9, and the upstream caspase signal chemokine, RANTES (CCR5), are expressed in lateral temporal cortical and hippocampal neurons [37].…”
Section: Heparin Sulfate (Glucosamine) 3-o-sulfotransferase 3a1 (Hs3smentioning
confidence: 99%
“…These cells usually express CXCR4 and CCR5, but rarely the CD4 molecule and the mechanism of entry into trophoblasts have still to be elucidated. Furthermore, it is still under debate whether the varying expression levels of CCR5 on placental cells may augment the risk of MTCT of HIV-1 (Joubert et al 2010). Instead, it was clearly shown that the interaction and fusion between trophoblastic cells and HIV-1-infected cells allow the virus to cross the trophoblastic barrier in an in vitro model.…”
Section: In Utero Transmission: the Role Of The Placentamentioning
confidence: 99%